Profiles of people in power the world's government leaders - East, Roger; Thomas, Richard, 1977- (2006)
A reference guide to head's of government around the globe. Covering some 200 countries and territories, it profiles every serving head of state and head of government and explains both, the role of the head of state, head of government and the legislature as well as each country's type of government.